Estudo genético e aspectos reprodutivos em espécies do gênero Physalis - Santos, Keylla Souza dos (2018)
The genus Physalis L. belongs to the Solanaceae family. Its center of diversity is found in Mexico, where two-thirds of the species are endemic.The importance of the species that comprise this genus is mainly related to the production of substances of pharmacological interest. In addition to the medicinal properties, the genus also stands out because it contains species that produce fruits with high commercial value.Considering the importance of the species that make up the genus Physalis, this work aimed to study two species of this genus (Physalis ixocarpa, green and purple varieties, and Physalis philadelphica) from a genetic, cytogenetic and reproductive point of view. Cytogenetic studies revealed that, in meiosis, the chromosomes of the species studied show a regular pattern of division, resulting in good pollen viability observed.For the study that evaluated the viability of pollen and the receptivity of the stigma, throughout the day, it was observed that the pollen grains of both species presented good viability throughout the day, however, new studies must be carried out to determine the more efficient culture for the germination of the pollen tube in Physalis species.With respect to stigmatic receptivity, it is recommended that hybridization to P. ixocarpa verde can be performed at any time of the day, and in P. philadelphica and P. ixocarpa roxa it is recommended that the hybridization be performed in the afternoon.Regarding the study of genetic parameters, correlations and divergence, it was verified that: the highest CVg (%) were obtained for PMF and AT. The PMF, DLT, DTF and AT characteristics presented high heritability values allowing selection gains.Positive, highly significant correlations were observed for the PMF x DTF characters, and positive and significant for the DLF x DTF characteristics, by the t test. The Mantel correlation test showed highly significant positive correlations for PMF x DL, PMF x DT, DL x DT, PTF x NF, PTF x AT and NF x AT. Finally, the Toucher method was more sensitive for the species discrimination, since it allowed to isolate P. philadelphlca from P. ixocarpa.The DTF, AT and DLF variables presented the greatest contributions to the genetic divergence.